2015
DOI: 10.1371/journal.pone.0121823
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference of Myocyte Enhancer Factor 2A Accelerates Atherosclerosis in Apolipoprotein E-Deficient Mice

Abstract: ObjectiveMyocyte enhancer factor-2A (MEF 2A) has been shown to be involved in atherosclerotic lesion development, but its role in preexisting lesions is still unclear. In the present study we aim to assess the role of MEF 2A in the progression of pre-existing atherosclerosis.MethodsEighty apolipoprotein E-deficient mice (APOE KO) were randomly allocated to control, scramble and MEF 2A RNA interference (RNAi) groups, and constrictive collars were used to induce plaque formation. Six weeks after surgery, lentivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…More importantly, the combined interference of Lp-PLA 2 and YKL-40 reduces local inflammation more efficiently than the selective interference of Lp-PLA 2 or YKL-40 alone. These results are in agreement with our previous studies showing that atherosclerosis is a multifactorial process intertwined with inflammation [ 1 , 2 , 5 ]. In addition, several lines of evidence have demonstrated that high circulating levels of YKL-40 are associated with increased MCP-1, IL-6, and TNF-α levels and macrophage recruitment in plaques [ 7 , 12 15 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…More importantly, the combined interference of Lp-PLA 2 and YKL-40 reduces local inflammation more efficiently than the selective interference of Lp-PLA 2 or YKL-40 alone. These results are in agreement with our previous studies showing that atherosclerosis is a multifactorial process intertwined with inflammation [ 1 , 2 , 5 ]. In addition, several lines of evidence have demonstrated that high circulating levels of YKL-40 are associated with increased MCP-1, IL-6, and TNF-α levels and macrophage recruitment in plaques [ 7 , 12 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…The propensity to rupture is based on structural characteristics of lesions [ 22 ]. Evidences suggest that thicker fibrous cap, relative lower content of lipids, relative higher content of collagen are all indicators of plaque stability [ 1 , 2 , 4 , 5 ]. Finally, our data revealed that the plaque area for the combined Lp-PLA 2 and YKL-40 RNAi group was only moderately lower than that of the Lp-PLA 2 RNAi group, and this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further in vitro studies confirmed that cZNF609 acted as miR-615-5p, bonded to Ago2, the core part of RNA induced silencing complex (RISC), inhibited the expression of myocyte enhancer factor 2A(MEF2A) transcription factor and Tie2, a tyrosine-protein kinase that acts as cell-surface receptor for angiopoietins during angiogenesis, ECs survival, increased OS, ECs dysfunction and migration in HUVECs. However, researchers have shown that alteration of MEF2A and Tie2 accelerated vascular inflammation by activating proinflammatory signaling, macrophage infiltration, ECs dysfunction and AS in apoE deficiency mice [ 11 , [84] , [85] , [86] , [87] ].…”
Section: Abnormalities In Dna and Histone In Asmentioning
confidence: 99%